The Conflict Management at Workplace through Positive Social Change lead to the Social Equilibrium and Supply Chain Performance of Baduy Society Based Food Supply Companies - Budiaman, Budiaman; Umasih, Umasih; Mukhtar, Saparuddin; Rudi Casmana, Asep (ExcelingTech, 2020)
This study aims to find out empirically the role of conflict resolution through societal change to promote SCP in food supply companies working in Baduy community in Kanekes Village, Leuwidamar District, Lebak Regency. Furthermore, the mediating role of conflict management and social equilibrium was also examined. In this direction social change is considered as an important factor to promote SCP. This study used a quantitative research approach based on the survey questionnaire. For this purpose, data were collected from the employees of food supply companies working in Baduy community. The results of the study show that the causes of conflict in the food supply companies are internal factors and external factors. Social change has positive effect on conflict management at workplace in food supply companies. Increase in the social change increases the conflict management which further enhances the social equilibrium and ultimately increases the SCP. Finally, results of the current study have vital role in food supply companies to enhance the SCP.